THE GERIATRIC ANXIETY SCALE AND THE GERIATRIC ANXIETY INVENTORY: RELATIONSHIPS TO ANXIETY RISK FACTORS. (11th November 2018) - Noel, O; Pifer, M; Mahoney, C; Segal, D
Abstract: Anxiety in later life is a major clinical problem, with notable barriers to accurate assessment. The Geriatric Anxiety Scale (GAS) and Geriatric Anxiety Inventory (GAI) represent two elder-specific assessment tools that have recently been developed and validated. This study aimed to examine the convergent validity of both measures as they relate to known risk factors for anxiety and to directly compare the measures. Community-dwelling older adults completed the GAS, GAI, and four measures that cover three anxiety risk factors: the Mindful Attention Awareness Scale (MAAS), the Kentucky Inventory of Mindfulness Skills (KIMS), the Acceptance and Action Questionnaire-II (AAQ-II), and the Anxiety Sensitivity Index-3 (ASI-3). Correlations were computed between the GAS and the GAI with the risk factors. Results showed that the GAS and GAI were both significantly and strongly negatively associated with mindfulness as measured by the MAAS (-.69, -.72) and the KIMS (-.54, -.58), showing that higher anxiety was associated with lower mindfulness, as expected. The GAS (.70) and GAI (.76) were both significantly and strongly positively associated with experiential avoidance (AAQ-II), showing that higher anxiety was associated with higher avoidance, as expected. Likewise, the GAS (.37) and GAI (.54) were both significantly and moderately positively associated with anxiety sensitivity (ASI-3), showing that higher anxiety was associated with higher anxiety sensitivity, as expected. For each of these risk factors, there were no significant differences between the correlations for the GAS and the GAI, showing that both measures performed well but with no meaningful advantages of one over the other.